Ghosts: Season Three Season 3 - BBC Studios; Kingsley, Tom, 1985-; Carpenter, Alison; Daughton, Kate; Haywards, Debra; Owen, Alison, 1961-; Adefope, Lolly, 1990-; Baynton, Mathew, 1980-; Farnaby, Simon; Willbond, Ben, 1973-; Howick, Jim; Rickard, Laurence, 1975-; et al. (London, England : BBC Studios, 2022)
Alison and Mike are working hard to bring their new 'guest house' plans to fruition, when the peace is disrupted by an unexpected visitor who arrives with a life-changing revelation. Alison questions everything she thought she knew, and the ghosts react with varying degrees of fear, mistrust, and in some cases, delight. Meanwhile, Mike is more intent than ever to put Button House on the map while trying to hold onto his day job.
Title from disc surface.
Originally broadcast as single episodes of a television program in 2019.
Wide screen.
Bonus feature: Season 3 Bloopers.
new dvd 2023 spring.
Lolly Adefope, Mathew Baynton, Simon Farnaby, Martha Howe-douglas, Jim Howick, Laurence Rickard, Charlotte Ritchie, Ben Willbond.
Keywords: Haunted houses -- Drama; Hotels -- Drama; Haunted houses; Hotels; Drama; Television programs; Video recordings; Television programs for the hearing impaired; Comedy television programs